Oxygenation and Semi-Fowler Position to Improve Breathing Patterns in Clients with Acute Decompensated Heart Failure (ADHF) - Rizki Mauludiya; Indah Dwi Pratiwi (Jurnal Kesehatan dan Kedokteran, 2026)
Acute Decompensated Heart Failure (ADHF) is a cardiovascular emergency commonly characterized by dyspnea, orthopnea, the use of accessory respiratory muscles, and decreased oxygen saturation. These conditions occur due to increased left ventricular pressure and pulmonary congestion, which may lead to an ineffective breathing pattern and require prompt and appropriate nursing interventions. Objective: This study aimed to evaluate the effectiveness of combining oxygen therapy using a nasal cannula and the Semi-Fowler position in improving the breathing pattern of patients with ADHF. Methodology: This research employed a case study design involving three patients treated in the Intensive Cardiac Care Unit (ICCU) of Kanjuruhan Hospital, Malang. Data were collected through clinical observation of respiratory parameters, including dyspnea, orthopnea, use of accessory muscles, respiratory rate, and oxygen saturation over three days of intervention. The data were analyzed descriptively by comparing patients’ conditions before and after the intervention. Findings: The results showed significant improvement in respiratory patterns beginning on the second day, indicated by reduced dyspnea and orthopnea, the absence of accessory muscle use, decreased respiratory rate approaching the normal range, and increased oxygen saturation above 94%. By the third day, all patients demonstrated optimal improvement across all respiratory indicators. Implications: These findings suggest that the combination of oxygen therapy and the Semi-Fowler position can serve as an effective, simple, and practical nursing strategy to reduce respiratory workload, enhance lung expansion, and optimize ventilation–perfusion mechanisms in ADHF patients, particularly in intensive care settings. Originality: This study contributes to the existing literature by highlighting the effectiveness of combining two basic non-invasive nursing interventions in managing ineffective breathing patterns in ADHF patients, thereby reinforcing evidence-based nursing practices in intensive cardiovascular care.